2000
DOI: 10.1149/1.1393386
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of Chemical Mechanical Polishing Processes Using a Discretized Geometry Approach

Abstract: A transport‐based, three‐dimensional numerical modeling approach has been developed to simulate chemical mechanical polishing processes occurring in microelectronic materials processing. A unique aspect of this model is that the detailed morphology of the slurry flow domain between the wafer and polishing pad is approximated with a regularly updated sequence of geometries evenly positioned along the polishing orbit. Additionally, the modeling approach allows the use of any constitutive relationship for the rhe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“…Based on the understanding of the CMP process, researchers have modeled the feature scale surface evolution in different ways: some of the researchers (e.g., Runnels [11] and Yao et al [18]) assume that there is a fluid layer between the wafer and the pad while the others group assumes solid-to-solid contact. For the latter, there are also two kinds of models: one implies only high areas on the wafer feature have direct contact with pad and low areas are free of any loading and is not polished (e.g., Chekina [1], Elbel et al [3], and Saka et al [12]); the other assumes both high and low areas contact with the pad (e.g., Chen and Lee [2] and Vlassak [16]).…”
mentioning
confidence: 99%
“…Based on the understanding of the CMP process, researchers have modeled the feature scale surface evolution in different ways: some of the researchers (e.g., Runnels [11] and Yao et al [18]) assume that there is a fluid layer between the wafer and the pad while the others group assumes solid-to-solid contact. For the latter, there are also two kinds of models: one implies only high areas on the wafer feature have direct contact with pad and low areas are free of any loading and is not polished (e.g., Chekina [1], Elbel et al [3], and Saka et al [12]); the other assumes both high and low areas contact with the pad (e.g., Chen and Lee [2] and Vlassak [16]).…”
mentioning
confidence: 99%
“…Fluid mechanics: The effect of flowfield and hydrodynamic pressure of the slurry was not taken into account in this model. Past models have suggested that the slurry shear rate directly affects the wear of the wafer sample [1,26,27], while other studies have shown that the sample contact stress is affected by the slurry hydrodynamic pressure [35,36]. Neither of such assumptions are taken into account in the current model.…”
Section: Modeling Assumptionsmentioning
confidence: 97%
“…3. Pad roughness: Following the pattern of past featurescale CMP models [21,25,26], the authors chose to omit pad roughness effects from the model in this study. In addition to making this assumption for simplicity purposes, it must be noted that the scale of the feature of interest (L = 70 lm) could be considered to be small enough to minimize large-scale pad roughness effects, since the asperity density of polishing pads is typically around g = 10 -5 asperities/lm 2 [12,39].…”
Section: Modeling Assumptionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the understanding of the CMP process, researchers have modeled the feature scale surface evolution in two different ways: one group (e.g., Runnels 1996 andYao et al 2000) assumes there is a fluid layer between wafer and pad while the other group assumes direct wafer-pad contact. For the latter, there are also two kinds of models: one implies only high areas on the wafer feature have direct contact with pad and low areas are free of any loading and is not polished (e.g., Elbel et al 1998, Chekina 1998and Saka et al 2001; the other assumes both high and low areas contact with pad (e.g., Gotkis et al 1998, Chen and Lee 1999, Vlassak 2001and Saka et al 2001.…”
Section: Literature Reviewmentioning
confidence: 99%